Gases emission during the continuous thermophilic composting of dairy manure amended with activated oil shale semicoke. (15th July 2021) - Li, Xu; Shi, Xiaoshuang; Feng, Quan; Lu, Mingyi; Lian, Shujuan; Zhang, Mengdan; Peng, Hui; Guo, Rongbo
Abstract: NH3 and greenhouse gases emission are big problems during composting, which can cause great nitrogen nutrient loss and environmental pollution. This study investigated effects of the porous bulking agent of oil shale semicoke and its activated material on the gases emission during the continuous thermophilic composting. Results showed addition of semicoke could significantly reduce the NH3 emission by 74.65% due to its great adsorption capacity to NH4 + -N and NH3, further the effect could be enhanced to 85.92% when utilizing the activated semicoke with larger pore volume and specific surface area. In addition, the CH4 emission in the semicoke and activated semicoke group was also greatly mitigated, with a reduction of 67.23% and 87.62% respectively, while the N2 O emission was significantly increased by 93.14% and 100.82%. Quantification analysis of the functional genes found the abundance of mcrA was high at the massive CH4 -producing stage and the archaeal amoA was dominant at the N2 O-producing stage in all the composting groups. Correlation and redundancy analysis suggested there was a positive correlation between the CH4 emission and mcrA . Addition of semicoke especially activated semicoke could reduce the CH4 production by inhibiting the methanogens. For the NH3 and N2 O, it was closely related with the nitrification process conducted by archaeal amoA . Addition of semicoke especially activated semicoke was beneficial for the growth of ammonia-oxidizing archaea, causing the less NH4 + -N transformation to NH3 but more N2 O emission. Graphical abstract: Image 1 Highlights: Addition of semicoke could reduce NH3 and CH4 emission during composting. Addition of semicoke could cause more N2 O generation during composting. Activated semicoke could further reduce NH3 and CH4 emission, but increase N2 O. CH4 emission was directly related to the functional genes of mcrA in the pile. NH3 and CH4 emission was closely related to the archaeal amoA gene.